Emerging evangelicals : faith, modernity, and the desire for authenticity - Bielo, James S. (New York University Press, 2011)
The Emerging Church movement developed in the mid-1990s among primarily white, urban, middle-class pastors and laity who were disenchanted with America's conservative Evangelical sub-culture. It is a response to the increasing divide between conservative Evangelicals and concerned critics who strongly oppose what they consider overly slick, corporate, and consumerist versions of faith. A core feature of their response is a challenge to traditional congregational models, often focusing on new church plants and creating networks of related house churches. Drawing on three years of ethnographic f.